Recalling The Lost Essence: Identity And Sexuality In Lars Von Trier's Breaking The Waves - Antaridha, Rabbi (CV. ITTC INDONESIA, 2025)
Lars von Trier's Breaking the Waves (1996) succeeded in initiating polarizing arguments concentrated on the tragic fate of its central heroin, Bess. The violent misogynistic treatments she receives from the society in her village—governed by a deeply patriarchal institution—could not be discounted. However, the experimentation of sexual roles in a heterosexual relationship in patriarchy conducted in the film is another interesting source of analysis. The film proposes a reversed concept of sexual subject/object and orchestrates a certain situation where such anomaly morphs into an extremely instrumental aspect to the main characters' (Bess' and Jan's) beings and fates. In this study, the dynamics of Jan's idea about object and power, his act of assuming the concept of sexual object as his identity, his loss of physical ability and the power, and his attempt at recalling the lost essence through an eccentric request is analyzed by employing Foucault's concepts of power/knowledge and arts of existence. The utilized methods of analysis are close reading and textual analysis in which the material object’s elements or components as well as their relationships are closely examined based on certain theoretical framework. This study found that Jan is demonstrating the decentralized nature of power, in this case sexual power, in the face of essentializing patriarchal ideas about sexual subject/object and male/female sexual identities through his identification as a sexual object despite of being a male in a patriarchal society.